2022
DOI: 10.1093/mnras/stac2604
|View full text |Cite
|
Sign up to set email alerts
|

Variability due to climate and chemistry in observations of oxygenated Earth-analogue exoplanets

Abstract: The Great Oxidation Event was a period during which Earth’s atmospheric oxygen (O2) concentrations increased from ∼10−5 times its present atmospheric level (PAL) to near modern levels, marking the start of the Proterozoic geological eon 2.4 billion years ago. Using WACCM6, an Earth System Model, we simulate the atmosphere of Earth-analogue exoplanets with O2 mixing ratios between 0.1 per cent and 150 per cent PAL. Using these simulations, we calculate the reflection/emission spectra over multiple orbits using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 86 publications
4
9
0
Order By: Relevance
“…Two other recent studies 22,23 also exploited 3-D chemistry-climate models like in our case, however the main focuses of these studies have been different to ours and the linearity of the O3/O2 relationship has only briefly been touched. One of these studies showed a continuously linear O3/O2 relationship up to the present atmospheric level and to the one experiment that they performed with higher-than-present O2 (31.5%) 22 , whereas the other one showed a clear saturation of the O3/O2 relationship around the present level 23 , which is consistent with us, however with no experiments beyond that. Unfortunately, both studies haven't presented and discussed the details of their ozone and temperature changes in the stratosphere, which complicates the identification of potential reasons for this disagreement.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Two other recent studies 22,23 also exploited 3-D chemistry-climate models like in our case, however the main focuses of these studies have been different to ours and the linearity of the O3/O2 relationship has only briefly been touched. One of these studies showed a continuously linear O3/O2 relationship up to the present atmospheric level and to the one experiment that they performed with higher-than-present O2 (31.5%) 22 , whereas the other one showed a clear saturation of the O3/O2 relationship around the present level 23 , which is consistent with us, however with no experiments beyond that. Unfortunately, both studies haven't presented and discussed the details of their ozone and temperature changes in the stratosphere, which complicates the identification of potential reasons for this disagreement.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…1a, however, with a maximum O3 concentration reached at ~10.5% O2 20 or ~5.25-11.55% O2 21 . Other 3-D modeling studies showed a similar shape to us up to the present O2 level but were either not performed for higher than present O2 cases 23 or showed a different, continuously increasing pattern 22 . Previous studies discussed several mechanisms responsible for the obtained shapes, however none of them interpreted their results from the point of view of feedbacks of chemistry with the middle atmospheric dynamics.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…For truly terrestrial worlds such as TRAPPIST-1 e and f, simulated detections suggest spectral features of CO 2 , CH 4 , and N 2 O features at the 4.3, 3.3, and 8.5 μm bands will be feasible within 30 transits for near-term observations by the JWST (e.g., Fauchez et al 2019;Lustig-Yaeger et al 2019;Wunderlich et al 2020;Kaltenegger & Lin 2021;Lustig-Yaeger et al 2022;Mikal-Evans 2022). In the next few years, more potentially habitable planets will be discovered, with the catalog of these systems to date in the order of hundreds and growing; models of various complexities and heritages are just on the rise and will quantitatively evaluate their inhabitance or habitability (Méndez et al 2020;Fauchez et al 2021;Wordsworth & Kreidberg 2022;Cooke et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Photochemical modeling of rocky exoplanets was first performed in one-dimensional (1D) models (e.g., Segura et al 2005;Kaltenegger & Sasselov 2009;Segura et al 2010;Hu et al 2012;Grenfell et al 2013;Gao et al 2015;Kozakis et al 2018) that provided key insights into the effects of stellar spectral energy distribution, stellar variability, and stellar flares. More recently, such modeling efforts have been expanded to the 2D and 3D regimes, usually with atmospheric chemistry and photochemistry as additional subcomponents in global Earth system or general circulation models (Chen et al 2018(Chen et al , 2019(Chen et al , 2021Braam et al 2022;Cooke et al 2022;Ridgway et al 2023;Tsai et al 2022). While the efficiency of single-column models allows one to explore a large parameter space of planetary characteristics, higher dimensional (2D/3D) models are able to simulate the complex interplay among atmospheric dynamics, clouds, radiation, and chemistry and hence provide results with enhanced realism.…”
Section: Introductionmentioning
confidence: 99%